2008
DOI: 10.1109/jstqe.2008.915526
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Self-Frequency Shift: Experimental Demonstrations and Applications

Abstract: Soliton self-frequency shift (SSFS), a consequence of Raman self-pumping that continuously redshifts a soliton pulse, has been widely studied recently for applications to fiber-based sources and signal processing. In this paper, the fundamentals of SSFS are reviewed. Various fiber platforms for SSFS (single-mode fiber, microstructured fiber, and higher order mode fiber) are presented and experimental SSFS demonstrations in these fibers are discussed. Observation of Cerenkov radiation in fibers exhibiting SSFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(53 citation statements)
references
References 82 publications
0
49
0
Order By: Relevance
“…It has been shown that pulses generated via SSFS are usually chirp-free, with nearly transform-limited duration [23]. Nevertheless, we verified the pulse shape and duration via interferometric autocorrelation using a standard Michelson interferometer with a 2-mm thick BBO crystal for second harmonic generation (SHG).…”
Section: Ocis Codes: (1403070) Infrared and Far-infrared Lasers; (19mentioning
confidence: 90%
“…It has been shown that pulses generated via SSFS are usually chirp-free, with nearly transform-limited duration [23]. Nevertheless, we verified the pulse shape and duration via interferometric autocorrelation using a standard Michelson interferometer with a 2-mm thick BBO crystal for second harmonic generation (SHG).…”
Section: Ocis Codes: (1403070) Infrared and Far-infrared Lasers; (19mentioning
confidence: 90%
“…In the case of spatial soliton the natural property of light which is to disperse in space is being compensated by the nonlinearity of the medium in such a way that higher intensity part of an optical beam which is typically at the center of the employed Gaussian beam, increase a value of refractive index of medium forming de facto a core of waveguide that is responsible to confine in reverse a dispersed light to the middle of the beam itself [5]. It can be easily intuitively understood that if the self induced nonlinearity [2] is too high the beam will get focused and on the other hand if it is very small or none, beam will disperse in space -a prevailing situation in many cases where a beam does not have enough power density to induce nonlinearity in a medium.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, solitons suffers various higher order effects like third order dispersion (Elgin et al 1995), intra pulse Raman scattering (Golles et al 1997) and self steepening (Lee 2008;Voronin and Zheltikov 2008;Trippenbach and Band 1998) which needs precise control on system design. The Third Order Dispersion (TOD, β 3 ) can be treated as perturbatively small at longer region from zero dispersion point, but becomes a matter of interest at or near zero dispersion point of the optical fiber.…”
mentioning
confidence: 99%